Study of Inhibition DNA Polymerase by Phenolic Compounds in Traditional Food Spices on the Polymerase Chain Reaction Process - Fadila Abna Swari; Suharti, Suharti; Evi Susanti; Eli Hendrik Sanjaya; Sumari, Sumari (Tinta Emas Publisher, 2023)
Polymerase Chain Reaction (PCR) is a repeated cycle process including denaturation, annealing and extension using the DNA polymerase enzyme. This identification method is based on specific DNA which increases the number of DNA strands millions of times. The aim of this study was to identify and classify phenolic group compounds in traditional food spices that have the potential to inhibit DNA polymerase and their mechanism of action in the PCR process. The observation made was the Literature Review study as an analytical test method regarding the study of DNA polymerase inhibition by phenolic group compounds in traditional food spices in the PCR process. The results of this study were analyzed from several appropriate literature studies showing that most of the spices in traditional foods contain secondary metabolites of phenolic group compounds. These compounds have been shown to inhibit DNA polymerase in the PCR process, one of the mechanisms is to bind to the active site of DNA polymerase which causes decreased activity and deactivates DNA polymerase. Moreover, it can degrade and denaturate DNA polymerase. This makes it difficult to identify haram substances in processed food products using PCR.